2017
DOI: 10.1021/acs.joc.7b01498
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Intrinsically Blue-Colored bis-Nitronyl Nitroxide Peptidomimetic Templates and Their Conformational Preferences as Revealed by a Combined Spectroscopic Analysis

Abstract: The intrinsically blue-colored Ullman imidazolinyl nitronyl nitroxide (NN) mono-radicals have found various applications, in particular as spin probes and organic magnetic materials. Here, we present the solution-phase synthesis, extensive characterization, and conformational analysis of the first peptidomimetics with two pendant, chiral nitronyl nitroxide free radical units. Two (R)-Aic(NN) residues, where Aic(NN) is 2-amino-5-nitronylnitroxide-indan-2-carboxylic acid, have been inserted at positions i and i+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This discrimination of 3 10 - and α-helices by VCD was a significant advance since neither CD nor IR spectra could reliably characterize 3 10 -helices. A number of studies with various mixed sequences and alternative α,α-disubstituted residues showed these patterns to be consistent, see Figure , bottom, middle. , Even some quite small Aib n peptides, n = 4, 5, showed VCD patterns reflecting 3 10 formation as did sequences with other α,α-disubstituted residues. , Sequences with alternate Aib-Pro residues create a so-called β-bend ribbon that is similar in φ, ψ conformation to a 3 10 helix but lacks half the internal H-bonds. This structure also has VCD similar to that of the 3 10 helices, providing another example of VCD’s ability to sense the torsional conformation independent of variations in residues or side chains, or even complete H-bonding patterns .…”
Section: Empirical Peptide Voa Studies Correlation Of Spectra With Se...mentioning
confidence: 84%
“…This discrimination of 3 10 - and α-helices by VCD was a significant advance since neither CD nor IR spectra could reliably characterize 3 10 -helices. A number of studies with various mixed sequences and alternative α,α-disubstituted residues showed these patterns to be consistent, see Figure , bottom, middle. , Even some quite small Aib n peptides, n = 4, 5, showed VCD patterns reflecting 3 10 formation as did sequences with other α,α-disubstituted residues. , Sequences with alternate Aib-Pro residues create a so-called β-bend ribbon that is similar in φ, ψ conformation to a 3 10 helix but lacks half the internal H-bonds. This structure also has VCD similar to that of the 3 10 helices, providing another example of VCD’s ability to sense the torsional conformation independent of variations in residues or side chains, or even complete H-bonding patterns .…”
Section: Empirical Peptide Voa Studies Correlation Of Spectra With Se...mentioning
confidence: 84%
“…Among nitroxides, nitronyl (NN) and imino nitroxide (IN) radicals are proven to be a versatile family of spin labels as NNs are transformed into INs by reactive radicals generated in biological processes or decay completely to diamagnetic species; both cases can be easily monitored thanks to distinctive pattern in their EPR spectra (Joseph et al, 1993;Rosen et al, 2003;Medvedeva et al, 2004;Samuni et al, 2010;Wang et al, 2011;Sousa et al, 2016). NN and IN based spin probes are ideally suited for investigating the dynamic aspects of molecular interactions because of their covalent incorporation into biologically critical architectures (Okamoto et al, 2005;Ise et al, 2006;Tanaka et al, 2007;Maekawa et al, 2007Maekawa et al, , 2010Atsumi et al, 2012;Wright et al, 2014;De Zotti et al, 2017) and noncovalent interactions (Nakabayashi et al, 2007;Peresypkina et al, 2010;Vostrikova et al, 2011;Kobayashi et al, 2014Kobayashi et al, , 2018Strizhakov et al, 2014). On the other hand, nitrile-containing compounds are known to form protein-ligand interactions by hydrogen bonding, hydrophobic interactions and covalent bonding with numerous protein residues (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%